Ракурсы прояснения смысла в литературном произведении (на материале рассказа И.А. Бунина Камарг) - Подковырин, Юрий (Conversatoria Litteraria, 2021)
The article focuses on the interpretation of Ivan Bunin’s short story under the title "Kamarg". The main emphasis is laid on various ways of clarifying the meaning: first, for characters in the story, secondly, for the author and readers. Since the meaning remains "in the darkness", i.e. hidden from the characters, the author shows how semantic "darkness" of the short story can be clarified by the creative efforts of the author and readers.